Primary Axillary Lipogranuloma in a Patient With Systemic Lupus Erythematosus - Suk Jung Kim (Archives of Rheumatology, 2014)
Lipogranuloma is an uncommon inflammatory reactive process related to endogenous or exogenous lipid materials. Although lipogranuloma most frequently involves the penis and scrotum of young adults, it may affect many other organs. This report describes primary axillary lipogranuloma in a 45-year-old woman with systemic lupus erythematosus in the light of the mammographic and ultrasonographic findings of this rare entity. This is the first report of primary axillary lipogranuloma in the literature in English.